2018
DOI: 10.1089/zeb.2018.1620
|View full text |Cite
|
Sign up to set email alerts
|

Chromosome Spreading of the Retrotransposable Rex-3 Element and Microsatellite Repeats in Karyotypes of the Ancistrus Populations

Abstract: The repetitive DNAs are the expressive substrate to genomic evolution and directly related to chromosomal diversification in eukaryote, including fishes. Ancistrus is an interesting group for studies about interplay between repetitive DNA and karyotype evolution, given its extensive chromosomal variation. In this study, we aimed to understand the evolutionary dynamics in genome of the distinct Ancistrus populations of the Paraná basin to the contribution of three classes of repetitive DNA sequences. Nucleotide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 47 publications
1
10
0
Order By: Relevance
“…These heterochromatin regions are often associated with the accumulation of repetitive sequences such as microsatellite repeats, as evidenced in several fish species, like Astroblepus grixalvii Humboldt, 1805, Astroblepus homodon Regan, 1904[Conde-Saldanã et al, 2019, Scleropages leichardti Günther, 1864, Scleropages formosus Müller & Schlegel, 1840 [Cioffi et al, 2019], Osteoglossum bicirrhosum Cuvier, 1829, and Osteoglossum ferreirai Kanazawa, 1966 [Souza et al, 2019]. The association of microsatellite clusters with heterochromatin regions and differentiated sex chromosomes is relatively common among Ancistrini species [Prizon et al, 2018]. However, in P. tankei these sequences may have a structural role, since they showed the same pattern in all individuals analyzed (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…These heterochromatin regions are often associated with the accumulation of repetitive sequences such as microsatellite repeats, as evidenced in several fish species, like Astroblepus grixalvii Humboldt, 1805, Astroblepus homodon Regan, 1904[Conde-Saldanã et al, 2019, Scleropages leichardti Günther, 1864, Scleropages formosus Müller & Schlegel, 1840 [Cioffi et al, 2019], Osteoglossum bicirrhosum Cuvier, 1829, and Osteoglossum ferreirai Kanazawa, 1966 [Souza et al, 2019]. The association of microsatellite clusters with heterochromatin regions and differentiated sex chromosomes is relatively common among Ancistrini species [Prizon et al, 2018]. However, in P. tankei these sequences may have a structural role, since they showed the same pattern in all individuals analyzed (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, as revealed here in our study, even with ancient origin, they can also be found practically intact in recent lineages, where the X and Y of R. rufipes are undistinguished from each other, with the Y sex chromosome being identified solely by comparative genomic hybridization and recruitment of several SSR motifs. The sex chromosomes may remain undifferentiated for many reasons, for example, transitions and turnovers involving XY and ZW, evolutionary advantages promoted by the recombination between XY and/or Z and W, as well as shifts involving autosomes [ 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , …”
Section: Discussionmentioning
confidence: 99%
“…SSR landscapes and their genome-wide distribution may inherently impact on chromosomal architecture; for instance, they are one of the major promoters of the expansion and/or contraction of repetitive sequences with which they are associated [73,74], for instance, transposable elements and rDNAs [63,75,76]. Here, we found at least three SSRs (GT, AG, AAC) bearing 18S rDNA of the 3rd pair, with minute differences in size, sometimes in both males and females (not shown in the figures), suggesting that these small repeats (di-and trinucleotides) are likely involved in regulatory processes, reflective of uneven crossing and ectopic recombination mediated by the association of such SSRs and the activity of the ribosomal sites.…”
Section: Discussionmentioning
confidence: 99%
“…The genus Ancistrus Kner, 1854 (Hypostominae, Ancistrini) occurs from Panama to Argentina, presenting 65 valid species, in addition to distinct lineages not formally identified in the scientific literature due to its taxonomic complexity ( Ferraris, 2007 ; Armbruster, 2008 ; Prizon et al, 2018 ; Borba et al, 2019 ; Fricke et al, 2021 ). From a chromosomal point of view, Ancistrus represents one of the most diverse lineages of Loricariidae, emphasizing their extensive variation in the diploid number (2n = 34 to 54, Supplementary Table S1 ).…”
Section: Introductionmentioning
confidence: 99%
“…Sex chromosomes in Ancistrus have been evidenced by size heteromorphism and accumulation of heterochromatic regions ( Mariotto et al, 2004 ; Alves et al, 2006 ; Mariotto and Miyazawa, 2006 ; de Oliveira et al, 2007 ; de Oliveira et al, 2008 ; de Oliveira et al, 2009 ). Recently, in situ localization of repetitive sequences have provided insights into the differentiation of these chromosomes in several groups of fish, including Ancistrus ( Cioffi and Bertollo, 2010 ; Schemberger et al, 2014 ; Cioffi et al, 2014 ; Favarato et al, 2017 ; Prizon et al, 2018 ; Schemberger et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%